Operational Phase–Resolved HIRARC Framework for Occupational Pesticide Risk Characterization and Mitigation - Basri, Syahrul (Universitas Islam Negeri Alauddin Makassar, 2026)
The use of pesticides in the agricultural sector plays a critical role in supporting food security; however, it simultaneously poses substantial risks to human health and the environment. This article aims to analyze occupational risks associated with pesticide use among farmers using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) framework. Through a structured literature review and synthesis of four case studies, the findings indicate that pesticide exposure generates physical, chemical, biological, and environmental hazards with risk levels ranging from moderate to very high. These risks are exacerbated by inadequate use of personal protective equipment (PPE), limited occupational safety training, and substandard working conditions. The reviewed evidence demonstrates chronic health impacts, including decreased cholinesterase enzyme activity, elevated heavy metal concentrations in farmers’ biological samples, and high dermal exposure levels during pesticide mixing and loading activities. The analysis further identifies critical exposure nodes linked to specific work phases, underscoring the importance of activity-based risk characterization in informal agricultural settings. To address these challenges, this article proposes a field-activity-based HIRARC scenario as a practical analytical tool for systematic risk evaluation in small-scale and informal farming systems. Effective risk control requires a holistic intervention strategy encompassing safety education, improved access to certified PPE, regulatory reinforcement, and community-based as well as technology-supported approaches.